Ecology of inshore notothenioid fish from the Danco Coast, Antarctic Peninsula - Casaux, Ricardo Jorge; Barrera Oro, Esteban; Baroni, Paola Andrea; Ramon, Analia Ines (Polar Biology)
A total of 1103 inshore notothenioid fish were caught by means of trammel-nets in four sites surrounding Cierva Point (Moss Island 1; Moss Island 2; Sterneck Island and Leopardo Island), Danco Coast, West Antarctic Peninsula, during February and March 2000. The families Nototheniidae, Channichthyidae and Bathydraconidae were represented in the samples being Notothenia coriiceps the dominant fish of the area. Gobionotothen gibberifrons and Trematomus newnesi followed in importance. In general, the fish sampled agreed in terms of number and mass with that of the South Shetland Islands area, except for a marked higher occurrence of G. gibberifrons in the Danco Coast. This supports the hypothesis that the commercial fishery around the South Shetland Islands at the end of the 1970s was responsible for the decrease in the inshore population of G. gibberifrons in that area during the last seventeen years. Information on morphometry, reproduction and diet of the fish species caught is provided. Fil: Casaux, Ricardo Jorge. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Barrera Oro, Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Baroni, Paola Andrea. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Ramon, Analia Ines. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata; Argentina